Paracoccidioidomycosis manifested by sarcoidosis-like cutaneous lesions and caused by Paracoccidioides brasiliensis sensu stricto (S1a) - Marques, Silvio Alencar [UNESP]; Scotton Jorge, Marilia Formentini [UNESP]; Hrycyk, Marluce Francisca [UNESP]; Gimenes Bosco, Sandra de Moraes [UNESP] (Soc Brasileira Dermatologia, 2018)
Molecular studies have shown more than one species of the genus Paracoccidioides to be the causal agent of paracoccidioidomycosis. Efforts have been made to correlate the identified species with epidemiological and clinical data of patients, aiming to determine the real meaning and impact of new species. Bearing this objective in mind, the authors report a clinical case of paracoccidioidomycosis, from Sao Paulo state, Brazil, that manifested as uncommon sarcoid-like cutaneous lesions and was caused by Paracoccidioides brasiliensis sensu stricto (S1a). The patient was treated with itrawnazole 200mg/day for 12 months, with complete clinical remission.
Keywords: Paracoccidioidomycosis; Sarcoidosis; Skin diseases; Skin manifestations